2019
DOI: 10.4049/jimmunol.1801161
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of Macrophage Migration Inhibitory Factor Promotes Inflammatory Bone Resorption Induced in a Mouse Model of Periradicular Periodontitis

Abstract: Locally produced osteoclastogenic factor RANKL plays a critical role in the development of bone resorption in periradicular periodontitis. However, because RANKL is also required for healthy bone remodeling, it is plausible that a costimulatory molecule that upregulates RANKL production in inflammatory periradicular periodontitis may be involved in the pathogenic bone loss processes. We hypothesized that macrophage migration inhibitory factor (MIF) would play a role in upregulating the RANKL-mediated osteoclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 54 publications
3
34
0
Order By: Relevance
“…On the other hand, a cell culture study demonstrated that the RANK and RANKL factors are not sufficient for the firm and static union between osteoblasts and osteoclasts and that the ICAM-1/LFA molecules are necessary to the effective adhesion between these cells during the osteoclastogenesis (Okada et al 2002). However, those present in vivo findings confirm the requirement of RANKL expressed on osteoblasts for osteoclasts maturation and the crucial involvement of the RANK and RANKL in periapical lesion development, as previously described (Vernal et al 2006, Bezerra da Silva et al 2014, Braz-Silva et al 2018, Francisconi et al 2019, Howait et al 2019, Jakovljevic et al 2019. These osteoclastogenesis mediators were increased in the larger periapical lesions of the KO mice, even in the absence of an important adhesion molecule.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…On the other hand, a cell culture study demonstrated that the RANK and RANKL factors are not sufficient for the firm and static union between osteoblasts and osteoclasts and that the ICAM-1/LFA molecules are necessary to the effective adhesion between these cells during the osteoclastogenesis (Okada et al 2002). However, those present in vivo findings confirm the requirement of RANKL expressed on osteoblasts for osteoclasts maturation and the crucial involvement of the RANK and RANKL in periapical lesion development, as previously described (Vernal et al 2006, Bezerra da Silva et al 2014, Braz-Silva et al 2018, Francisconi et al 2019, Howait et al 2019, Jakovljevic et al 2019. These osteoclastogenesis mediators were increased in the larger periapical lesions of the KO mice, even in the absence of an important adhesion molecule.…”
Section: Discussionsupporting
confidence: 83%
“…However, those present in vivo findings confirm the requirement of RANKL expressed on osteoblasts for osteoclasts maturation and the crucial involvement of the RANK and RANKL in periapical lesion development, as previously described (Vernal et al , Bezerra da Silva et al , Braz‐Silva et al , Francisconi et al . , Howait et al , Jakovljevic et al ). These osteoclastogenesis mediators were increased in the larger periapical lesions of the KO mice, even in the absence of an important adhesion molecule.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations